THE INFLUENCE OF DIVIDEND POLICY ON STOCK PRICE (CASE STUDY IN PT TOTAL BANGUN PERSADA TBK) - yani, putri; Huda, Nurul (Jurnal Ekonomi Balance, 2020)
The purpose of this study was to determine the effect of dividend policy on stock prices (a case study at PT totalangun persada Tbk). The population of this research is the financial statements of dividend policy and share prices (case study at PT totalangun persada Tbk), for 10 years, namely 2009 - 2018. angun persada Tbk), for 5 years, namely 2014 - 2018. This research is an associative study with a sampling technique, namely purposive sampling. The test results show that there is a significant influence between dividend policy on stock prices (a case study at PT totalangun persada Tbk). With a R2 value of 10.8%.